Life expectancy, death, and disability in Haiti, 1990-2017: a systematic analysis from the Global Burden of Disease Study 2017 - Fato Fene; María Jesús Ríos-Blancas; James Lachaud; Christian Razo; Hector Lamadrid-Figueroa; Michael Liu; Jacob Michel; Roody Thermidor; Rafael Lozano (Revista Panamericana de Salud Pública, 2020)
Objective. To investigate the magnitude and distribution of the main causes of death, disability, and risk factors in Haiti. Methods. We conducted an ecological analysis, using data estimated from the Global Burden of Disease Study 2017 for the period 1990-2017, to present life expectancy (LE), healthy life expectancy (HALE) at under 1-year-old, cause-specific deaths, years of life lost (YLLs), years lived with disability (YLDs), disability adjusted life-years (DALYs), and risk factors associated with DALYs. Results. LE and HALE increased substantially in Haiti. People may hope to live longer in 2017, but in poor health. The Caribbean countries had significantly lower YLLs rates than Haiti for ischemic heart disease, stroke, lower respiratory infections, and diarrheal diseases. Road injuries were the leading cause of DALYs for people aged 5-14 years. Road injuries and HIV/AIDS were the leading causes of DALYs for men and women aged 15-49 years, respectively. Ischemic heart disease was the main cause of DALYs for people older than 50 years. Maternal and child malnutrition were the leading risk factors for DALYs in both sexes. Conclusion. Haiti faces a double burden of disease. Infectious diseases continue to be an issue, while non-communicable diseases have become a significant burden of disease. More attention must also be focused on the increase in worrying public health issues such as road injuries, exposure to forces of nature and HIV/AIDS in specific age groups. To address the burden of disease, sustained actions are needed to promote better health in Haiti and countries with similar challenges.